71 Long-term Outcomes of Coarctation of Aorta in East of England – The Norfolk and Norwich and Papworth Hospital Experience. (3rd June 2016) - Rafiq, Isma; Flather, Marcus; Abraham, Dilip; Freeman, Leisa J
Abstract : Background: Coarctation of the aorta (CoA) is associated with premature mortality with a mean survival age of 35 year in spite of early repair. Treatment paradigms are continually changing and contemporary data on CoA are needed. Methods: The Norwich and Papworth (NORPAP) dataset was set up in 1993 to record demographics, treatments and outcomes of adult congenital heart disease (ACHD) patients in the east of England. We report on the CoA subset. Results: In total 2322 patients were included in the dataset and of these 223 had CoA (9%): 146 males and 77 females, mean age 40 years (range 16–94). Hypertension was documented in 34% and coronary heart disease 6%. 91% received a corrective procedure (80% surgical and 11% percutaneous) and of these 38% required more than one procedure. Percutaneous intervention made up about half of all re-do procedures. 13% of second procedures were not related to CoA and were mostly aortic valve replacement. There were two case of subarachnoid haemorrhage and 2 deaths (0.8%) over approximately 10 years follow up. Conclusion: There is a high initial intervention rate in CoA with about 40% requiring additional intervention. The serious complication rate was low in our cohort suggesting that prognosis is improving over time.